PENERAPAN KLAUSULA EKSONERASI DALAM PERJANJIAN PENITIPAN BARANG DI HOTEL BERBINTANG V (STUDI PADA HOTEL SAHID JAYA JAKARTA) - Norbaiti Norbaiti (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTIONThe extent of the deposit liabilities RECIPIENTS singer hung from the following: Fill their approval Yang has promised; Purpose And Individual Contract Nature ITU. Apart from the breadth of storage Goods issue consignment, section 1706 gives affirmation as a guideline: RECIPIENT deposit required to "maintain" as befits her surrogate Goods Goods maintain Alone. Maintenance obligations entrusted goods, starting from the Establishment Contract and Delivery of Goods. Maintenance and hearts did he "should not apply passip". Maintenance Not Work As then Saja. But it should be made WITH Maintenance Safety That Gives Certainty differences of Goods, According WITH contents and nature of the agreement Yang accompanied ATTITUDE Good faith. Goods in Custody Agreement in Grand Elty do Operates written and poured hearts Custody Form for Goods. Contents And Form for each AT DIFFERENT depending starred hotels. Nevertheless ON generally consists From Identity penitip, (name, address, number ROOM And Sign serbi, Custody number, date / time Decision As well as the name and Signs About Custody Officer Yang ACCEPT). Besides IT AT-Star Hotel in Grand Elty The prayer System using the key ON Care Goods, written magnitude replace Losses Should be replaced by parties Hotel When eliminating key carries. There are some important HAL The content of the agreement is NOT listed hearts Care Goods at Hotel Grand Elty. Between lay, NOT mentioned Remedies In Case of damage / loss of goods whose entrusted Due to Errors Officers Hotel And Losses The magnitude of dressing received penitip. Goods in Custody Agreement Hotels Only Applies For The Guest Room hire Hotel, HAL singer can Seen ON Card Custody Receipt Goods Which Must therein specified number ROOMS The guest in question.Searching Google Pages approval of the agreement ROOMS Hotel Hence arises the rights and obligations of the parties to carry out the review Achievement. One is get the right tenant for the Protection of Goods luggage. The rights set hearts of Article 1709 of the Civil Code and Article 28 of the Decree of the Director General of Tourism No. 14 / U / II / 98. Some of the rights to the reviews get Protection Against The goods has fulfilled By Leader Hotel Namely WITH disediakannya Care Goods. But in one of the parties of their rights eliminated Alone By Leader Hotel WITH existence exoneration clause The deployment of IN Guest Card And Forms Services Directive. Custody exoneration clause intended Item Also dihotel By Leader Hotel to review the contents of the agreement supports the Custody of goods subject to ADA IN Custody Form Item. Besides the clause hearts ITU ABOUT Also notified their storage Safe Goods. As for the obligation of notifying shown to the Leader Hotel Guest Hotel to review storing luggage storage place Valuable Treasures Provided Hotel, has set hearts of article 29 paragraph (2) Decision of the Director General of Tourism. On one side of the Good BECAUSE THINGS is a prayer One Form responsibility Against the Safety Leadership Awards goods the Guests That WITH let them know where the safe box. But unfortunately HAL is followed or preceded BY clause of exoneration